Association of Elevated Plasma Total Homocysteine With Dementia With Lewy Bodies: A Case-Control Study - Zhang, Guili; Liu, Shuai; Chen, Zhichao; Shi, Zhihong; Hu, Wenzheng; Ma, Lingyun; Wang, Xiaodan; Li, Xudong; Ji, Yong (Frontiers in Aging Neuroscience, 2021)
Background: Elevated plasma total homocysteine (tHcy) level, a known risk factor for vascular disease, is reported to be an independent risk factor for cognitive impairment and Alzheimer’s disease (AD) in most studies. tHcy may also be associated with dementia with Lewy bodies (DLB). Objective: To investigate the association between plasma tHcy levels and DLB or AD. Methods: This is a case-control study including 132 DLB patients, 264 AD patients and 295 age-matched healthy controls. We used multivariate logistic regression model to analyze the data with adjustments for confounding variables. Results: The highest tHcy tertile (>13.9 µmol/L) was significantly independently associated with DLB (adjusted odds ratio (OR): 4.65, 95% confidence interval (CI): 1.95-11.10, P = 0.001) and AD (adjusted OR: 1.82, 95% CI: 1.02-3.23, P = 0.041) compared to the lowest tertile (<10.7 µmol/L). The cumulative frequency plots showed a shift in the distribution of the tHcy concentrations to higher values in patients with DLB compared to AD. The mean tHcy levels were stable and not altered by duration of cognitive impairment prior to the collection of blood samples from DLB patients. Conclusion: Elevated plasma tHcy levels were independently associated with DLB, and the association was stronger for DLB than for AD. The lack of a relationship between tHcy levels and symptom duration may refute these observed associations being a consequence of DLB, and future longitudinal studies will be required to confirm whether tHcy plays a causative role in DLB.